2018
DOI: 10.1016/j.preghy.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of labetalol and nifedipine MR on blood pressure in women with chronic hypertension in pregnancy

Abstract: There are significant and important differences between the BP lowering effects of nifedipine and labetalol. A large randomised control trial is required to investigate the relationship between BP variability and time in target on pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…99 Furthermore, they have been shown superior to methyldopa in regard to controlling blood pressure 20 and are possibly safer than labetalol in regard to controlling blood pressure to a safely low diastolic pressure. 91 One randomized controlled clinical trial compared oral nifedipine and labetalol in pregnant women with chronic hypertension. A central aortic pressure drop of mean 7.4 mmHg was seen in the nifedipine arm, but peripheral blood pressures were effectively the same in both arms.…”
Section: Treatment Of Choice—non-severe Hypertensionmentioning
confidence: 99%
“…99 Furthermore, they have been shown superior to methyldopa in regard to controlling blood pressure 20 and are possibly safer than labetalol in regard to controlling blood pressure to a safely low diastolic pressure. 91 One randomized controlled clinical trial compared oral nifedipine and labetalol in pregnant women with chronic hypertension. A central aortic pressure drop of mean 7.4 mmHg was seen in the nifedipine arm, but peripheral blood pressures were effectively the same in both arms.…”
Section: Treatment Of Choice—non-severe Hypertensionmentioning
confidence: 99%
“…В более ранних рандомизированных исследованиях, непосредственно сравнивавших его с метилдопой, не было обнаружено его преимуществ в отношении безопасности и эффективности [38,39], а в другом исследовании показано пограничное превосходство лабеталола в профилактике протеинурии, тяжелой АГ и госпитализаций во время беременности; лабеталол также был независимо связан с меньшим количеством совокупных неблагоприятных материнских и перинатальных событий [40]. Кроме того, исследование, в котором сравнивались амбулаторные показатели АД у беременных, принимающих перорально лабеталол или нифедипин замедленного высвобождения, продемонстрировало, что в группе лабеталола отмечалось более частое снижение ДАД ниже 80 мм рт.ст., что может ассоциироваться с ухудшением маточно-плацентарной перфузии [41]. β-адреноблокаторы (β-АБ) считаются препаратами первого ряда в Канаде (ацебутолол, метопролол, пиндолол, пропранолол) [4].…”
Section: определение и классификацияunclassified
“…It has a short half-life (4 to 6 hours), requiring dosing to be split to two to three times per day, which can contribute to difficulties with adherence. A study that examined the impact of gestation on the pharmacokinetics of labetalol found a significant increase in the oral clearance rate across gestation and when compared with the oral clearance rate outside pregnancy, which might explain the findings of a recent mechanistic study that showed that pregnant women prescribed labetalol, compared with nifedipine, had greater variation in blood pressure over 24 hours 14,15. Possible adverse effects include lethargy, weakness and somnolence, and it is relatively contraindicated in women with asthma as it can cause bronchospasm.Labetalol is the only antihypertensive agent that holds a Medicines and Healthcare Regulatory Agency licence for use in pregnancy, but this is primarily a reflection of the difficulties and apathy surrounding licensing drugs for use in pregnancy.…”
Section: Evidence For Labetalol For Gestational Hypertension and Pre-mentioning
confidence: 99%